Handbook of warning intelligence - Grabo, Cynthia M.; Goldman, Jan (Security and professional intelligence education series, 2015)
The Handbook was written during the cold war and was classified for 40 years. Originally written as a manual for training intelligence analysts, it explains the fundamentals of intelligence analysis and forecasting, discusses military analysis, as well as the difficulties in understanding political, civil, and economic analysis and assessing what it means for analysts to have ""warning judgment."" This new edition includes the final ten chapters recently released by the government. This is the manuscript as it was originally intended to be published by the author in 1972.